Communication Effectiveness of Acculturation of Migrant Students with Local Communities (Case Study of Communication Studies Students at the State Islamic University of North Sumatra) - Syecha Bawazier; Icha Ariyana; Taufiq Sarfan Hasibuan; Maulana Andinata Dalimunthe; Hasan Sazali (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2022)
Cultural exchange is very likely to happen, because anyone who comes from a country or region will certainly not be separated from the culture in which he was born and raised. With a culture rooted in him, he had to share a room with other people from other cultures. This cultural exchange, may be causing a conflict. Conflict can be muted with the birth of an awareness that every person should be able to understand the culture of other people of different cultures with him. The process of communication that takes place between people of different cultures is often influenced by several factors: The Act, The Scene, The Agent (Performer), The Agency (Intermediaries), and The Purpose. The factors mentioned above also becomes one of determining an effective communication process. Based on that, we can determine the strategies or methods of communication used in a communication process. Effective communication can be realized if the strategies and methods of communication are used appropriately. Efektive communication strategy is very important to be considered in a process of communication. Intercultural communication as a form of interpersonal communication of communicators and communicant of different cultures. Effectiveness of interpersonal communication was largely determined by factors: openness, empathy, positive feelings, provide support, and maintain balance. While the social prejudices that determine the three main factors, namely stereotypes, social distance, and discrimination. The relationship between prejudice to the communication very closely because of the prejudices assumed as the basis for the establishment of communication behavior.